2015
DOI: 10.1097/md.0000000000001937
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Transthroracic Echocardiograpy and Transcranial Doppler With Contrast Agent for Detection of Patent Foramen Ovale With or Without the Valsalva Maneuver

Abstract: Patent foramen ovale (PFO) is a remnant of the fetal circulation exist in 20% of the general population. The purpose of our study was to compare of transthoracic echocardiography (TTE) and contrast-transcranial Doppler sonography (c-TCD) in the diagnosis and quantification of PFO with or without the Valsalva maneuver (VM).We studied 106 patients with a high clinical suspicion for PFO prospectively. Simultaneous c-TCD and TTE were conducted using agitated saline solution to detect right to left shunt (RLS). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…Maffè et al had reported that cTTE and cTCD had comparable sensitivity compared with TEE, with TEE as the reference standard, 89% for TTE, and 85% for TCD (Kühl et al, ; Maffè et al, ; Souteyrand et al, ). These are consistent with the results of our present study (González‐Alujas et al, ; Jong‐Won et al, ; Zhao et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Maffè et al had reported that cTTE and cTCD had comparable sensitivity compared with TEE, with TEE as the reference standard, 89% for TTE, and 85% for TCD (Kühl et al, ; Maffè et al, ; Souteyrand et al, ). These are consistent with the results of our present study (González‐Alujas et al, ; Jong‐Won et al, ; Zhao et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…During VM, contrast agent was injected 5 s before the start of VM. This was produced by the patients blowing into a small soft plastic tube connected to the manometer device, patients then started the VM on the examiner's command and held it for 5 s.We assessed the effective VM by monitoring the peak flow velocity of the MCA Doppler spectrum was decreased by at least 25%, and the manometer device achieved and maintained a pressure of 40 mm Hg [12]. When TTE detected micro-bubbles signals (MES) in the left atrium within 3 ~ 5 cardiac cycles, and TCD detected more than 1 MES appeared within 10 seconds after VM, then we regarded the c-TCD results as positive.…”
Section: Synchronous Test Of C-tte and C-tcdmentioning
confidence: 99%
“…The incidence of single breech pregnancy was 3-4% [1][2][3]. Due to increased risk of injury to the neonate during attempted vaginal delivery, 90% of full-term breech-presenting pregnancy women may have to choose cesarean section [4,5]. ECV is encouraged to reposition the fetus to a vertex presentation to avoid cesarean delivery [6], which is also considered as a cost-effective breech treatment with few complications.…”
Section: Introductionmentioning
confidence: 99%